Penggunaan Tanda Tangan Berubah-Ubah oleh Pejabat Pembuat Akta Tanah (Ppat) di dalam Pembuatan Akta - Faiz, Muhammad (Universitas Ekasakti, 2023)
This study discusses the use of arbitrary signatures by land deed officials (PPAT) in making deed. The object of this research is PPAT officials who are involved in making land deeds. The type of research in this research is normative, namely the type of research that uses secondary data (from the library) combined with primary data obtained by conducting field research, such as observations, interviews and surveys. The technique of collecting legal materials in this research was carried out by means of document studies or literature research, namely studies that examine various related documents, both statutory regulations and other documents. The material obtained is then processed and analyzed qualitatively, then presented descriptively, namely by explaining, describing and giving an overview in words of the findings from research that prioritizes the quality of the data. In analyzing legal materials, it begins with collecting legal materials and non-legal materials needed to answer the problem formulation. Both legal materials and non-legal materials are related to each other and then analyzed to find answers to the two problem formulations set forth in the research results and discussion chapter. The results of this study are: 1) The legal consequences of using a signature that changes by the PPAT in making a deed, then this is still justified by law. A different or changing signature is justified by law as long as the PPAT who affixes the signature confirms that it is his signature; 2) What is meant by perfect legal force of proof is that the evidence no longer needs to be supplemented or supported by other evidence.